The effect of ionising radiation upon the cellular DNA - Roszkowski, Krzysztof; Foksiński, Marek (Contemporary Oncology/Współczesna Onkologia, 2005)
Ionising radiation applied in the therapy of tumour diseases, are inducing formation of various DNA damages. This can interact with DNA molecules and evoke alkaline ionisation and this is the direct effect or through radiolysis of water molecules present in the cell and this is the indirect effect. The molecular structure of water breaks down radiolysis under the influence of radiation. As a result of the water radiolysis, a very aggressive hydroxyl radical ( • OH) arises. Numerous experimental data show that the hydroxyl radical is considered to be the main active form of oxygen responsible for the majority of DNA damages. The • OH radical attack upon DNA generates a whole range of DNA damage, among these modified bases. Some of these modified DNA bases have a considerable potential to damage the integrity of the genome. And the rise in the number of derivatives is the consequence of this process. Some of these lesions may lead to mutagenesis, carcinogenesis and reproductive cell death. Reaction with the chromatin DNA induces single and double-strand breaks in DNA. The free radicals generating in the direct neighbourhood of chromatin can lead to the creation of DNA-protein cross-link. Occurence of such damages leads to disorders of the chromatin structure, which can influence the processes of repair, replication and transcription of DNA in both normal cells and tumour. It is supposed that only the damage of coding places in DNA can make a lethal damage of a cell. Moreover, it is considered that parts of DNA devoid of nuclear proteins are most sensitive to damages caused by ionising radiation.